Principles of Extreme Mechanics (XM) in Design for Reliability (DfR) With Special Emphasis on Recent Advances in Materials Characterization and Experimentation Techniques - Budiman, Arief Suriadi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book addresses issues pertinent to mechanics and stress generation, especially in recent advanced cases of technology developments, spanning from micrometer interconnects in solar photovoltaics (PV), next-gen energy storage devices to multilayers of nano-scale composites enabling novel stretchable/flexible conductor technologies. In these cases, the mechanics of materials have been pushed to the extreme edges of human knowledge to enable cutting-edge, unprecedented functionalities and technological innovations. Synchrotron X-ray diffraction, in situ small-scale mechanical testing combined with physics-based computational modeling/simulation, has been widely used approaches to probe these mechanics of the materials at their extreme limits due to their recently discovered distinct advantages. The techniques discussed in this manuscript are highlights specially curated from the broad body of work recently reported in the literature, especially ones that the author had led the pursuits at the frontier himself. Extreme stress generation in these advanced material leads to often new failure modes, and hence, the reliability of the final product is directly affected. From the recent topics and various advanced case studies covered in this book, the reader gets an updated knowledge of how new mechanics can and has been applied in Design-for-Reliability (DfR) for some of the latest technological innovations known in our modern world. Further, this also helps in building better designs, which may avoid the pitfalls of the current practiced trends.
1. Introduction -- 2. Mechanics of Materials -- 3. Reliability of Devices, Technologies and Systems -- 4. Advanced Micro/Nanoelectronics, Microsystems and MEMS Devices and Technologies -- 5. Next Generation Energy Technologies and Systems -- 6. Conclusions.
Keywords: Mechanics, Applied; Solids; Materials$1 (BAnalysis.s; Mechanics; Solid Mechanics; Characterization and Analytical Technique; Classical Mechanics; Engineering design; Materials -- Mechanical properties; Reliability (Engineering)